The influence of extension activities on the competencies of traditional fisheries processing in Lampung Province: Pengaruh Penyuluhan terhadap Kompetensi Pengolah Perikanan Tradisional di Provinsi Lampung - Helvi Yanfika; Siti Amanah; Anna Fatchiya; Pang S. Asngari; Abdul Mutolib; Kordiyana K Rangga (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Extension is an informal learning process that plays an important role in improving fisheries processors competencies. However, current extension activities that have been running so far are felt to be lacking so it is necessary to look at the effectiveness of conducting extension on traditional fisheries business related to methods, media, materials and capabilities of extension agents. This study was aimed to (1) analyze the effectiveness of fisheries extension activities in traditional fisheries processing businesses in Lampung Province, (2) analyze traditional processors competencylevels, (3) analyze the effect of extension on processors competencies/capabilities in traditional fisheries processing businesses. This study used a quantitative approach enriched with qualitative analysis. The survey was conducted to obtain primary data using a questionnaire. The research location were in three districts in Lampung Province. The data analysis technique used descriptive and regression analysis. The results of the study were (1) the effectiveness of extension was still low, (2) traditional processors competencies belonged to the low category, and (3) the ability of extension agents affected the development of fisheries processors’ competencies. The effectiveness of extension is still low due to the limited extension methods. Therefore it is important to carry out extension activities with varied methods according to the target needs to improve the competency of traditional fisheries processors.